Refugees, Readmission Agreements, and “Safe” Third Countries: A Recipe for Refoulement? - Caron, Hallee (Journal of Regional Security, 2018)
As states in the global North have adapted to the changing nature of irregular immigration through the adoption of legal instruments such as readmission agreements, academics in international relations (IR) and international law as well as human rights organizations have responded by critiquing failed attempts at refugee protection, putting forward their own frameworks, and documenting human rights violations and/or breaches of international law. Drawing upon Jennifer Hyndman and Alison Mountz’s argument that current policies contribute to the externalization of asylum as well as Alexander Betts’s work on cross-persuasion, this paper argues that readmission agreements with “safe third country” clauses are inherently problematic in terms of refugee protection. Specifically, it examines the 1992 Readmission Agreement between Spain and Morocco as a way to investigate how these agreements work in practice as well as an illustration of how the North−South impasse (identified by Betts) is reified in international law. Focusing on readmission agreements with safe third country clauses and supplementing academic research on treaty interpretation and international law with analysis by policy experts and reports from human rights organizations, the analysis considers the consequences of third-party readmission agreements with regards to international cooperation on refugee protection.